Elderly's quality of life through social media technology: a netnography research / Nurfazlina Haris - Haris, Nurfazlina (2013)
The advantage of social media technology which to be connected with more people, indirectly bridge and bonding up the social capital between each of individuals such as elderly people and groups of community through the internet, have shown a perfect way to serve the purpose to make elder community to be more socially connected and increase the life performance in their life (Wright, 2000). Therefore the study on the elder in this study with a range over 55 years old to 70 on the higher end scale has been used. To conduct the study and investigate of the behavior among elder in the social media technology been proceeded by using the a qualitative method where ―Netnography‖ approach is suitable to investigate in depth with participant and observe, what makes elderly to be involved in the social media. Through the finding of the this study, the quality of life among elderly through the social media usage has been determine, from result of their behavior in the social media usage. The modified original Technology Acceptance Model (TAM) with additional of contruct of Perceive of Enjoyment and Perceive of Social Capital in this study was been act as guide to identified the perception and the behavior of the elderly towards social media where all of the participants are overall positively agreed on accepting the social media technology (Facebook) as perceived usefulness, perceive enjoyment, perceive ease of use, and perceive social capital and indirectly influence their behavior of intention to use the social media to technology. On the recommended part, on the future research, another researcher should carry on the study with another research methodology such quatify or quantitative research method to investigate and retest the the finding and result of this qualitative research. Other than that, the field of the study on the social media technology should be carry on a more focus and rich with interaction among its member such as Forum, Group or Blog type of social media technology.